2015
DOI: 10.1186/s13071-015-0967-2
|View full text |Cite
|
Sign up to set email alerts
|

Serological signature of tick-borne pathogens in Scandinavian brown bears over two decades

Abstract: BackgroundAnthropogenic disturbances are changing the geographic distribution of ticks and tick-borne diseases. Over the last few decades, the tick Ixodes ricinus has expanded its range and abundance considerably in northern Europe. Concurrently, the incidence of tick-borne diseases, such as Lyme borreliosis and tick-borne encephalitis, has increased in the human populations of the Scandinavian countries.MethodsWildlife populations can serve as sentinels for changes in the distribution of tick-borne diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Some reviews have suggested that B. burgdorferi sl can adaptively manipulate its Ixodes tick vector to enhance its own transmission, and hence the R 0 of Lyme borreliosis 11 , 28 . Ixodes ticks infected with B. burgdorferi sl differ from their uninfected counterparts in several phenotypes including questing behaviour, survival, body weight, and energy reserves 29 35 . However, most of these studies are correlational in nature, and there is a lack of controlled infection experiments investigating the effects of B. burgdorferi sl on the fitness of their tick vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Some reviews have suggested that B. burgdorferi sl can adaptively manipulate its Ixodes tick vector to enhance its own transmission, and hence the R 0 of Lyme borreliosis 11 , 28 . Ixodes ticks infected with B. burgdorferi sl differ from their uninfected counterparts in several phenotypes including questing behaviour, survival, body weight, and energy reserves 29 35 . However, most of these studies are correlational in nature, and there is a lack of controlled infection experiments investigating the effects of B. burgdorferi sl on the fitness of their tick vectors.…”
Section: Introductionmentioning
confidence: 99%
“…One such method is the detection of TBEV-specific antibodies in sentinel vertebrate hosts. Various wild and domestic vertebrates such as rodents [ 13 , 34 , 35 ], roe deer [ 36 ], goats [ 37 , 38 ], sheep [ 39 ], dogs [ 40 , 41 ], and even brown bears [ 42 ] have been used as sentinels in endemic areas. A disadvantage of this method is that detection of antibodies does not provide any information on the time and place of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of B. burgdorferi DNA in 321 black bears from Humboldt County, California was 26%. A serosurvey of 569 brown bears showed high antibody prevalence in brown bears from southern Scandinavia, whereas prevalence was lower in bears from Northern Scandinavia (Paillard et al, ).…”
Section: Bacterial Zoonosesmentioning
confidence: 99%
“…Additional antibodies to viral pathogens, like West Nile virus and related encephalitis viruses, have been detected in black bears in the United States and in brown bears in Europe, but bears are unlikely to play a significant role in those disease transmission cycles (Bronson et al, ; Farajollahi et al, ; Madić et al, ). Tick‐borne encephalitis virus was not detected in a serosurvey of brown bears from Scandinavia (Paillard et al, ).…”
Section: Viral Zoonosesmentioning
confidence: 99%